2005
DOI: 10.1093/jurban/jti088
|View full text |Cite
|
Sign up to set email alerts
|

HIV Among Injection Drug Users in Large US Metropolitan Areas, 1998

Abstract: This article estimates HIV prevalence rates among injection drug users (IDUs) in 95 large US metropolitan areas to facilitate social and policy analyses of HIV epidemics. HIV prevalence rates among IDUs in these metropolitan areas were calculated by taking the mean of two estimates: (1) estimates based on regression adjustments to Centers for Disease Control and Prevention (CDC) Voluntary HIV Counseling and Testing data and (2) estimates based on the ratio of the number of injectors living with HIV to the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 26 publications
5
45
0
1
Order By: Relevance
“…Friedman et al 22 estimated 1998 HIV prevalence rates among IDUs within the same 96 large MSAs as Holmberg. These estimates were based on (1) adjusting Centers for Disease Control (CDC) Counseling and Testing data by regression imputation techniques with research study data, and (2) estimates of the ratio of the number of IDUs living with HIV to the number of IDUs living in an MSA.…”
Section: Historical Data On Differences In Hiv Prevalence Among Idus mentioning
confidence: 99%
See 1 more Smart Citation
“…Friedman et al 22 estimated 1998 HIV prevalence rates among IDUs within the same 96 large MSAs as Holmberg. These estimates were based on (1) adjusting Centers for Disease Control (CDC) Counseling and Testing data by regression imputation techniques with research study data, and (2) estimates of the ratio of the number of IDUs living with HIV to the number of IDUs living in an MSA.…”
Section: Historical Data On Differences In Hiv Prevalence Among Idus mentioning
confidence: 99%
“…Dissimilarity in methods and problems of regression to (and from) the mean, limited our ability to study change in these estimates and makes interurban comparisons between Holmberg's 1992 21 estimates and Friedman's 1998 22 HIV prevalence estimates problematic. Developing our HIV prevalence rates among IDUs over time will enhance our capacity to study the determinants of changes in HIV epidemics.…”
Section: Historical Data On Differences In Hiv Prevalence Among Idus mentioning
confidence: 99%
“…5,6 Studies that have attempted to examine more precise associations between community characteristics and HIV infection among IDUs have found that income inequality at the standard metropolitan statistical area-level is associated with higher HIV prevalence among IDUs. [7][8][9] In a different study, residing in census tracts with high male unemployment was found to be associated with prevalent HIV among IDUs (income equality was not considered in this study). 10 In terms of HIV risk behaviors, a few studies have examined the association between community characteristics and injection-related HIV risk among IDUs.…”
Section: Introductionmentioning
confidence: 99%
“…CTS-based estimates may be affected by the extent to which the history of the local HIV epidemic varies across racial/ethnic groups of injectors. 85,86 For instance, in an MSA where HIV entered the local communities of Black injectors before it entered communities of White injectors, CTS-based estimates of Black IDU prevalence may be artificially low, given that HIV-positive individuals are unlikely to be retested. This bias, however, might be countered by frequent retests among HIVnegative Black injectors, who might be particularly concerned about HIV transmission.…”
Section: Limitations and Validationmentioning
confidence: 99%
“…1, 2, 3 and 4. Moreover, our capacity to adjust APIDSbased estimates for local HIV seroprevalence was limited given (1) our use of CTS data to calculate HIV seroprevalence, 70,85 and (2) spatial, temporal, and racial/ethnic variations in the time between HIV diagnosis and AIDS diagnosis, [62][63][64][65] variations that we could not adjust for. In addition, CDC reporting guidelines for APIDS and for CTS define injectors as anyone who has injected since 1978.…”
Section: Estimating Injection Drug Use Among Black and White Adultsmentioning
confidence: 99%